PENGARUH KOMPENSASI, LEVERAGE, UKURAN PERUSAHAAN , DAN DIVIDEN TERHADAP TURNOVER: STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN DI INDONESIA - EVY RAHMAN UTAMI; ETIK KRESNAWATI; EKA DWIYANTI PUTJE (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
This study aimed to show empirical evidence of the correlation between compensation, leverage, dividend and firm size with the CEO turnover of banking companies in Indonesia. This study used banking companies in 2009 – 2016. The total research samples were 41 companies. The data analysis used multiple regression. The result of the study indicated that compensation, leverage and firm size had no correlation with the CEO turnover of the banking companies. However, the dividend had positive and significance influence towards the CEO turnover of the directors. Compensation given to the board of directors were unable to align the interests of management and shareholders. Besides, the directors did not take leverage and total assets in the CEO turnover consideration. Nevertheless, they consider dividend distribution conducted by the company.